Radical Equations Calculator

Top

A radical eqquation is given below as default input for this calculator. Isolating and shifting the values of radical equation and squaring on both sides. The variable value of the radical equation is calculated on clicking "Solve Radical Equation".
**Step 1 :**

**Step 2 :**

**Step 3 :**

Radical is a symbol which is used to indicate square root or nth root. An equation that involves radicals are called radical equations.

**Radical Equation Calculator** calculates the value of the variable of the radical equation entered in the given space. This radical equation solver makes math full of fun. Radical equations calculator solves the given radical equations hence sometimes known as solving radical equations calculator or square root calculator with variables.

Input can be given in the following ways:

**sqrt(x + 3) + 4 = 5**

or

squareroot(x + 3) + 4 = 5

or

square root(x + 3) + 4 = 5.

Input can be given in the following ways:

or

squareroot(x + 3) + 4 = 5

or

square root(x + 3) + 4 = 5.

A radical eqquation is given below as default input for this calculator. Isolating and shifting the values of radical equation and squaring on both sides. The variable value of the radical equation is calculated on clicking "Solve Radical Equation".

Observe the given radical equation. Isolate one of the radical value by shifting all the other value to the right side.

Square the radical equation on both the sides.

Simplify the given equation to get the value of the variable.

Find the radical equation for the following:

$\sqrt{2x + 3}$ + 7 = 10

**Step 1 :**Given Radical equation is $\sqrt{2x + 3}$ + 7 = 10. Isolate the given radical expression by subtracting both sides by 7, we get

$\sqrt{2x + 3}$ + 7 - 7 = 10 - 7

$\sqrt{2x + 3}$ = 3**Step 2 :**Squaring the above equations on both the sides, we get

(2x + 3) = 9**Step 3 :**2x = 6

=> x = 3.**Answer :**The value of x is 3.

Simplify the given radical equations:

$\sqrt{x + 6}$ - $\sqrt{x + 2}$ = 4.

**Step 1 :**Given Radical equation is $\sqrt{x + 6}$ + $\sqrt{x + 2}$ = 4. Isolate the given radical expression, we get

$\sqrt{x + 6}$ = 4 + $\sqrt{x + 2}$

**Step 2 :**Squaring the above equations on both the sides, we get

(x + 6) = (4 + $\sqrt{x + 2}$)

^{2}

(x + 6) = 16 + (x + 2) + 8 $\sqrt{x + 2}$

(x + 6) - (x + 2) - 16 = 8 $\sqrt{x + 2}$

4 - 16 = 8 $\sqrt{x + 2}$

-12 = 8 $\sqrt{x + 2}$

Squaring on both the sides, we get

144 = 64 (x + 2)

144 = 64x + 128.

**Step 3 :**144 - 128 = 64x

16 = 64x

x = $\frac{1}{4}$

**Answer :**The value of x is $\frac{1}{4}$.